Jar of hearts [large type] - Hillier, Jennifer (Wheeler Publishing, a part of Gale, a Cengage Company, 2018)
When she was sixteen years old, Angela Wong disappeared without a trace. Nobody ever suspected that her best friend, Georgina Shaw, now an executive and rising star at her Seattle pharmaceutical company, was involved in any way. Certainly not Kaiser Brody, who was close with both girls back in high school. But fourteen years later, Angela Wong's remains are discovered in the woods near Geo's childhood home. And Kaiser, now a detective with Seattle PD, finally learns the truth.